2017
DOI: 10.1515/prolas-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Lignocellulose for Bioethanol Production

Abstract: Contributed by Alexander RapoportThe effect of temperature, time and amount of enzyme on hydrolysis of wheat straw lignocellulose remaining after furfural production was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…The trend shown in this study is compatible with those hypotheses. Similar results were also obtained for enzymatic hydrolysis of crop residues like sugarcane bagasse, corn straw, and wheat straw where the optimal reaction temperature for the enzyme is found to be between 50 °C and 55 °C 22, 23, 29, 30. They also stated, when the temperature was further increased beyond 55 °C, the concentration of reducing sugar was reduced 22, 23, 30.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The trend shown in this study is compatible with those hypotheses. Similar results were also obtained for enzymatic hydrolysis of crop residues like sugarcane bagasse, corn straw, and wheat straw where the optimal reaction temperature for the enzyme is found to be between 50 °C and 55 °C 22, 23, 29, 30. They also stated, when the temperature was further increased beyond 55 °C, the concentration of reducing sugar was reduced 22, 23, 30.…”
Section: Resultssupporting
confidence: 77%
“…Similar hydrolysis patterns have been reported for enzymatic hydrolases of lignocellulosic biomasses such as wheat straw [29], corn cob [40], rose petals [41], and pineapple leaves [20] for sugar production. Jaafar et al [35] and Basu et al [42] reported that the sugar production increased and observed a slight decrease after some time.…”
Section: Effect Of Reaction Timesupporting
confidence: 76%
See 2 more Smart Citations
“…Initially, enzymatic treatments aim to concentrate sugars so the fermentation process can increase its yield as glucose would be the substrate for the microorganisms to grow ( Vasic et al., 2021 ). Finally, the objective of thermal treatments is generally to either obtain biochar ( Rozenfelde et al., 2017 ) or products derived from pyrolysis ( Liang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%